Effect of Tuition Fee, Promotion on Number of Students: Trust as Mediation Variable - Anggy Qurnia Raafy Hasibuan (UPI YPTK Journal of Business and Economics, 2023)
This study examines the effect of tuition fees and promotions on the number of students at Dharmas Indonesia University (UNDHARI) through trust as an intervening variable. The research method used by researchers is a quantitative method using causality structural equations with the conception of the path analysis model research used to analyze patterns of relationships between variables to know the direct and indirect effects of independent (exogenous) variables on the dependent (endogenous) variable. Methods of data collection through surveys and distributing questionnaires, with a sample of 100 respondents. This study uses analytical toolsStructural Equation Modeling (SEM) using the program Partial Least Square (PLS). The research results found that, Tuition Fee a significant effect on trust. Promotion has no significant effect on trust. Tuition Fee significant effect on the number of students. The promotion has no significant effect on the number of students. Trust has a significant effect on the number of students. Trust mediates influence tuition Fee to the number of students. Trust mediates the effect of promotion on student enrollment.